Novel 3,19-(N-Phenyl-3-(4-fluorophenyl)-pyrazole) Acetal of Andrographolide Promotes Cell Cycle Arrest and Apoptosis in MDA-MB-231 Breast Cancer Cells - Siva Kumar Rokkam; Shahjalal Chowdhury; Yashwanth Inabathina; Lakshminath Sripada; Srinivas Nanduri; Balasubramanyam Karanam; Nageswara Rao Golakoti (Pharmaceuticals)
Background: Natural products play a crucial role in cancer treatment due to their ability to selectively target cancer cells. Andrographolide, a major constituent of Andrographis paniculata, exhibits potential anticancer properties. Considering the pharmacological importance of nitrogen-based heteroaromatic scaffolds, particularly pyrazole motifs, this study aimed to integrate the pyrazole pharmacophore with the andrographolide scaffold to develop novel therapeutic candidates. Methods: Twenty novel 3,19-(N-phenyl-3-aryl-pyrazole) acetals of andrographolide and isoandrographolide were synthesized and characterized using UV-Vis, FT-IR, NMR, and HRMS. Initial anticancer screening was conducted by the National Cancer Institute (NCI), USA, against 60 human cancer cell lines. The most promising compound, 1f (R = 4-F), was selected for further biological evaluation in the MDA-MB-231 breast cancer cell line. Results: The MTT assay results demonstrated that compound 1f exhibited strong, dose-dependent anti-proliferative effects. The apoptosis analysis of 1f revealed a time-dependent increase in apoptotic cells, and cell cycle studies indicated S phase arrest in MDA-MB-231 cells. Antioxidant activity via the DPPH assay identified compounds 1b (R = 3-NO2) and 2b (R = 3-NO2) as the most effective radical scavengers. The most active compounds were also evaluated for drug-likeness using in silico Lipinski’s rule assessments. Conclusions: The synthesized 3,19-(N-phenyl-3-aryl-pyrazole) acetals of andrographolide and isoandrographolide exhibited promising anticancer and antioxidant properties. Among them, compound 1f showed the most significant activity, supporting its potential as a lead candidate for further anticancer drug development.